Solubility analysis, cloning and functional overexpression of the lipase from aneurinibacillus thermoaerophilus strain HZ, the first member of true lipases subfamily I.9 - Masomian, Malihe; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (Springer, 2018)
Lipase from Aneurinibacillus thermoaerophilus strain HZ (HZ lipase) represents the first member of subfamily I.9 true lipases. The resultant of unique characteristics and structural features of HZ lipase has affirmed that subfamily I.9 is located between mesophilic and thermostable lipases. In advance to clone and express the HZ lipase gene, protein solubility of fusion HZ lipase was predicted and analyzed using different software. Then, to overexpress the target gene, high-level expression was performed in a prokaryotic system using different strains and vectors, and production conditions were optimized. HZ lipase was expressed under the control of strong and chemically inducible T7 promoter for high-level expression. It was fused to Trx-, His- and S-tags to solubilize the protein and also to specify and accelerate the purification procedure. The high amount of the HZ lipase protein was obtained as the soluble form (72.5 U/mL) using IPTG final concentration of 0.025 mM after 8 h induction at 30ºC. The expression was analyzed by SDS-PAGE and presence of His-tag was confirmed by Western blotting of protein. As the HZ lipase is the only member of subfamily I.9 that yet cloned and overexpressed, this procedure could be applied to the other close members.